Ramuan jamu herbal pada pakan terhadap performa pertumbuhan ikan nila (Oreochromis sp) - Pramono, Taufik Budhi; Marnani, Sri; Junaidi, Teuku; Setyawan, Agung Cahyo; Nasikhah, Ais Lulu; Wulan, Triana Sri (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2023)
Immunity and growth were problems in main focus in fish farming bussiness. The use of herbal ingredients in feed can be a solution. The aim of this research was to determine the effect of adding herbal supplements to feed in increasing the growth of Tilapia. The method used was a field experiment bya selecting tilapia in pond (8x3 m2). Adding natural supplements to feed begins with making herbal concoctions, then supplementing them with 50 mL/Kg feed..Fish were given feed at 3%/body weight for 1 month. The absolute growth in lenght and weight were 7.09Â±1.38 cm and 136.05Â±27.48 g. The feed conversation ratio was around 1.28, the feed efficiency was around 77.7% and the survival rate reached 100%. Herbal concoctions can increase immunity and optimal growth. .